Cultural Diversity in Al-Qur'an Perspective - Muhammad Tang; H Hasbullah; S Sudirman (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2018)
Cultural diversity is a necessity or is a Sunnatullah that occurs in human life. The existence of Allah SWT. Creating human beings with ethnicity and nationhood in essence created a diverse culture. We can see this in Indonesia, which is a pluralistic society, each tribe or region has its own cultural characteristics. To reveal the diversity of cultures the perspective of the Qur'an in this paper is used by Al-Farmawy's method of interpretation Al-Maudhui with a multi-interpretation approach (some interpretations that you use). This is intended to reveal the diversity of cultures in the Qur'an in a systematic and in-depth manner. With theological studies (based on al-Qur'an) on cultural diversity possessed by humans can strengthen faith by having an understanding that we have diversity and cultural differences between people. So as to foster awareness and mutual acceptance, respect and tolerance among fellow children. In the end, fostering a sense of unity and unity, the creation of a peaceful and peaceful society. Or the people of Baldatun Thoyyibah Wa Rabbun Ghofur.